Rancang Bangun Aplikasi Donor Darah Berbasis Mobile di PMI Kabupaten Bandung - Sugianto, Castaka Agus; Zundi, Teguh Muhammad (KOPERTIP : Jurnal Ilmiah Manajemen Informatika dan Komputer, 2017)
Blood donation is a voluntary process of giving blood for purposes of blood transfusion for others in need. Based on data from PMI in 2013 we still lack 600,000 liters of blood stocks. The process of delivering information related to blood donation, the community must always come PMI, so inefficient and less effective. Many who want to donate blood to help others, but because the information is still lacking, people do not know how to find out information, schedules and activities of existing blood donor. From the above problems, the author of the building android application design regarding blood donation, which is equipped with information / news donor activity, blood stock, schedules and locations, as well as a question and answer directly to the PMI. The methodology used to construct this system using the waterfall method and perform with Object Oriented design are visualized with UML include the Use Case Diagrams and Activity Diagrams. Results from reseach is the application of blood donors who are able to provide stock data bags of blood, donor activity schedules and locations, as well as a blood donor information, frequently asked questions with the PMI Bandung District online. Making it easier for users to be able to find out information about how, where, and terms requirements for blood donors.